Nanoparticles of Molecular Conductors and Superconductors: Progress Over the Last Ten Years. Issue 45 (14th October 2020) - Jacob, Kane; de Caro, Dominique; Faulmann, Christophe; Valade, Lydie
Abstract : We review conditions for growing molecular conductors and superconductors as nanoparticles, an attractive morphology for integrating them into electronic components or composite materials. Although the one‐dimensional character of these materials does not favor their growth as spheroidal objects, by adding growth controlling molecules to the reaction mixture, we succeeded in growing particles from 2 to 50 nm in size for fourteen systems. The choice of the growth controller depends on the nature of the chemical interactions it can establish with the reactive species to limit growth, and on the chemical or electrochemical synthesis procedure. We show that the chemical nature of the nanoparticles is alike single crystals. Due to resistive boundaries, conducting properties of nanoparticle powders are alike microcrystalline powders. Nevertheless, superconductivity occurs in three of the studied materials. The potential application of these nanomaterials is reported in four fields: composite materials, field‐effect transistors, thermoelectric components and biomedical materials. Abstract : Towards integrable nanoscale molecular conductors and superconductors: conditions for growing nanoparticles of 1D molecular conductors and superconductors are reviewed for fourteen compounds and their chemical and physical properties at nanoscale are compared to bulk ones. Examples of their potential integration into composites, OFETs, thermoelectric materials and biomaterials are described.